A STUDY OF THE SOCIAL AND ECONOMIC STATUS OF FISHERMEN IN GADCHIROLI DISTRICT - Kunghadkar, Amit Ramchandra; Kamble , Uttamchand Tukaram (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the social and economic status of fishermen in Gadchiroli district of Maharashtra, focusing on their livelihoods, living standards and essential resources. Despite the important role of fishing in the local economy, especially in rural and tribal areas, the socio-economic challenges faced by these communities are often overlooked. Using a mixed-methods approach, the research examines income levels, education, health, housing and the impact of government schemes such as the Pradhan Mantri Matsya Sampada Yojana (PMMSY) on improving their quality of life. The findings showed that while fishing is the primary source of livelihood, the community faces many challenges, including low income, limited access to education and health services, inadequate infrastructure and social neglect. Despite the implementation of welfare schemes, constraints like limited awareness and poor infrastructure hamper their effectiveness. The study concludes with recommendations for targeted policy interventions to enhance social and economic welfare of fishermen in Gadchiroli district with development of infrastructure facilities, skill acquisition programs and better healthcare and educational facilities. This research underlines the need for inclusive and effective policies for the development of fishing communities in rural India.